2019
DOI: 10.3390/agronomy9060318
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Sweet Potato (Ipomoea batatas (L.) Lam.) to Suppress Three Invasive Plant Species in Agroecosystems (Ageratum conyzoides L., Bidens pilosa L., and Galinsoga parviflora Cav.)

Abstract: Sweet potato (Ipomoea batatas (L.) Lam.) is a logical candidate crop to suppress invasive plants, but additional information is needed to support its potential application as a suppressive ground cover. The current study utilized a de Wit replacement series incorporating five ratios of sweet potato grown in the field in combination with one of three invasive plants (Ageratum conyzoides L., Bidens pilosa L., and Galinsoga parviflora Cav.) in replicated 9 m2 plots. Stem length, total biomass, and leaf area were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
2
24
0
1
Order By: Relevance
“…Under full sunlight, the leafstalk length and leaf area of A. adenophora progressively declined with increasing proportions of H. tuberosus , whereas those of H. tuberosus significantly increased with increasing proportions of A. adenophora in mixed culture. Similarly, previous studies also showed that the leaf area and Pn of some invasive species were greatly reduced with I. batatas competition [ 31 , 35 , 36 ]. The plant growth, biomass, leaf chlorophyll content, photosynthetic rate, transpiration rate, water use efficiency, and stomatal conductance of A. trifida were significantly decreased by H. tuberosus competition in mixed culture [ 11 , 37 ].…”
Section: Discussionsupporting
confidence: 59%
“…Under full sunlight, the leafstalk length and leaf area of A. adenophora progressively declined with increasing proportions of H. tuberosus , whereas those of H. tuberosus significantly increased with increasing proportions of A. adenophora in mixed culture. Similarly, previous studies also showed that the leaf area and Pn of some invasive species were greatly reduced with I. batatas competition [ 31 , 35 , 36 ]. The plant growth, biomass, leaf chlorophyll content, photosynthetic rate, transpiration rate, water use efficiency, and stomatal conductance of A. trifida were significantly decreased by H. tuberosus competition in mixed culture [ 11 , 37 ].…”
Section: Discussionsupporting
confidence: 59%
“…The appearance of G. parviflora is often associated with changes in the agriculture of a given area [ 46 , 47 ]. Research is being carried out to find crop species capable of suppressing the invasion of this and other weeds in agroecosystems, e.g., sweet potato [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, once the leaf canopy has closed, most sweetpotato cultivars do an excellent job preventing soil erosion and suppressing weed growth through shading and allelopathy (Cavalcante et al, 2018;Seem et al, 2003;Walker et al, 1989). As such, sweetpotatoes have shown potential for controlling invasive plant species when used as a suppressive groundcover (Shen et al, 2015(Shen et al, , 2019. Although canopy coverage in sweetpotatoes typically approaches 100% well before harvest (Labonte et al, 1999), there are differences among genotypes in how long this takes, suggesting that sweetpotato clones may vary substantially in the weed-free interval required to produce maximum yields.…”
Section: Discussionmentioning
confidence: 99%